Influence of transhumance on the spread of Rhipicephalus microplus (Canestrini, 1888) in Benin - Adinci, Kossi Justin; Akpo, Yao; Sessou, Philippe; Yessinou, Roland Eric; Adehan, Safiou Bienvenu; Youssao, Abdou Karim Issaka; Assogba, Marc Napoléon; Farougou, Souaïbou (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Rhipicephalus microplus is a very invasive tick whose control is a current challenge. Its speed of propagation is favored by specific risk factors whose knowledge is an essential prerequisite for a good rather design of strategies to put in place for its control. This study consisted of evaluating the influence of transhumance on the spread of this tick in Benin. Materials and methods: To achieve this objective, two sets of tick sampling were carried out on five animals before and after transhumance in 80 autochthon herds from 8 municipalities in Benin. Results: The abundance of R. microplus varies significantly between breeding type, hosting type, period of ticks collection and between some of their interactions such as: breeding*period, hosting*period and breeding*hosting*period. In addition, the abundance of R. microplus according to each of these factors before transhumance differs significantly from the one observed after transhumance; the parasite load of R. microplus observed before transhumance is much higher than that observed after transhumance. Transhumance contributes to the spread of R. microplus in Benin. Conclusion: It represents a risk factor on which health risk managers could act in terms of surveillance and control of this cattle tick by carrying out the de-parasitage in the health campaign programs of transhumant animals. http://doi.org/10.5455/javar.2018.e272